Study of the cases of severe acute maternal morbidity at a tertiary care centre - Jamal, Shehla; Srivastava, Ruchi; Jain, Arpit; Chutani, Nimmi; Agarwal, Shelly; Mehta, Archana; Gupta, Samta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Reduction in the maternal morbidity has been the key strategy towards achievement of Millennium Development Goal. Despite exhaustive measures at all levels, the decline has been slow. WHO in 2007 established a technical working group to identify cases of severe acute maternal morbidity. It served dual goals to identify the causes and pointing out delays leading to SAMM. SAMM is now an established superior indicator of surviving women’s health and allows uniform comparisons. The present study was conducted with an aim to identify cases of SAMM at our centre. The objective is to determine the frequency of maternal near miss and conduct an epidemiological survey. Methods: This retrospective study was conducted in the department of Obstetrics and Gynecology and ICU of School of Medical Sciences and Research, Greater Noida, from November 2014 to October 2017. All the cases identified as SAMM, as per WHO 2009 criteria (modified according to the local protocol), were included in the study. Results: During the study period there were a total of 2252 delivery, out of which 2051 were live births. There were 123 SAMM cases and 47 were excluded out of study. So, study was done on 76 cases of SAMM, and on 11 maternal deaths in the study period. Calculated MNM incidence ratio was 37.05 per 1000 live births. A mortality index of 12.64% was calculated. MNM to maternal death ratio was 6.9:1. Major identifiable cause for SAMM was hypertension (35.5%)), followed by haemorrhage (18.4%). Haematologic system was the commonest organ system involved. 67.8% of the admissions were done in critical condition. Conclusions: Maternal mortality and SAMM cases shared characteristics, and study of SAMM cases can provide an insight into the causative etiology and give time for early intervention.